Differential methylation of E2 binding sites in episomal and integrated HPV 16 genomes in preinvasive and invasive cervical lesions. Issue 9 (26th November 2012) - Chaiwongkot, Arkom; Vinokurova, Svetlana; Pientong, Chamsai; Ekalaksananan, Tipaya; Kongyingyoes, Bunkerd; Kleebkaow, Pilaiwan; Chumworathayi, Bandit; Patarapadungkit, Natcha; Reuschenbach, Miriam; von Knebel Doeberitz, Magnus
Abstract Enhanced expression of the HPV 16 E6‐E7 oncogenes may trigger neoplastic transformation of the squamous epithelial cells at the uterine cervix. The HPV E2 protein is a key transcriptional regulator of the E6‐E7 genes. It binds to four E2 binding sites (E2BSs 1–4) in the viral upstream regulatory region (URR). Modification of E2 functions, for example, by methylation of E2BSs is hypothesized to trigger enhanced expression of the viral E6‐E7 oncogenes. In the majority of HPV‐transformed premalignant lesions and about half of cervical carcinomas HPV genomes persist in an extra‐chromosomal, episomal state, whereas they are integrated into host cells chromosomes in the remaining lesions. Here we compared the methylation profile of E2BSs 1–4 of the HPV 16 URR in a series of 18 HPV16‐positive premalignant lesions and 33 invasive cervical cancers. CpGs within the E2BSs 1, 3, and 4 were higher methylated in all lesions with only episomal HPV16 genomes compared with lesions displaying single integrated copies. Samples with multiple HPV16 integrated copies displayed high methylation levels for all CpGs suggesting that the majority of multiple copies were silenced by extensive methylation. These data support the hypothesis that differential methylation of the E2BSs 1, 3 and 4 is related to the activation of viral oncogene expression in cervical lesions as long as the viral genome remains in the episomal state. Once the virus becomes integrated into host cell chromosomes these methylation patterns may be substantially altered due to complex epigenetic changes of integrated HPV genomes.